Personalized System of Instruction Models Using â€œPOJOKâ€ Digital Module Based Toward Basket Ball Learning Outcome - Juditya, Silvy; Zakaria, Dhani Agusni; Hardi, Veny Juaniarni; Rusmana, Ruslan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The development of technology demands a lot of changes in the world of education, as well as in physical education learning so that physical education teachers in schools must be able to choose and apply learning models that can be juxtaposed with technology-based learning media, therefore the purpose of this study is to determine the effect of learning models. personalized system of instruction (PSI) based on the application of the electoral module "PJOK" on basketball learning outcomes. To achieve these objectives, the research method used is an experimental method with a one group pre-test-post-test design. The data source of this research involved in this study, namely 120 students aged 13-15 years at SMPN 8 Cimahi with purposive random sampling technique. The research instrument used was a basketball basic movement skills test instrument (ITKG BB) for ages 13-15. The data analysis used was paired simple t-test and the results of this study obtained a t-count value of 61.87 with a significance level of 0.00. Looking at the results of data analysis, the conclusion of this study is that there is an influence of the personalized system of instruction (PSI) learning model based on the application of the electoral module "PJOK" on basketball learning outcomes.Key words: Personalized System of Instructioned models (PSI), E-Modul, Basket Ball